Implementasi Manajemen Risiko Operasional Menggunakan ISO 31000 pada Yayasan Al Jihad Surabaya - Ardiansyah, Vicky; Sulaiman Tanjung, Sultan; Andriani Zakariya, Novie (Journal of Islamic Economics Studies and Practices, 2024)
This study discusses the development and implementation of operational risk management in non-profit organizations, specifically Al Jihad Foundation. The aim of this research is to identify the risks faced by the organization and propose strategies to minimize these risks. The study employs a qualitative approach through in-depth interviews with the foundation's management, following the risk management standards of ISO 31000. The results indicate that Al Jihad Foundation has begun to implement risk management principles, particularly in addressing operational challenges such as problematic tuition fee payments; however, further development is still needed, especially in long-term planning. The implications of this research highlight the importance of a more systematic approach to risk management in daily operations, which can enhance the organization's resilience.